ASSESSMENT OF MENTAL LOAD OF TECHNICAL SECTOR OF NURSING CLINICAL MEDICAL AND SURGICAL HOSPITAL OF THE UNIVERSITY OF THE WEST PARANÁ – HUOP (Fiep Bulletin - online, 2013)
The labor sphere has been transformed with new technologies, generating a faster pace workers. Increasingly, the work is taking a more cognitive content, which imposes extremely unhealthy conditions to human health as a whole. In the hospital if anything differs, workers are also exposed to unsanitary conditions and inadequate work ergonomically, and are exposed to other risks of biological or psychosocial. Favoring thus the rise of the diseases related mental load of workers. Thus, the present study aimed to verify the main mental load and identify possible stressors that trigger mental overload of nursing technicians who perform their duties in the field of medicine and surgery at the University Hospital of the West of Paraná - HUOP. Questionnaires were used to characterize the sample and to investigate the possible stressors that trigger mental overload. This questionnaire includes questions on work and organizational factors related to the worker's own function. And then answered the questionnaire NASA-TLX regarding mental load. Regarding data, demand got greater mental subscale. Moreover, the lack of sector employees and the number of patients on MV stressors were more pointed by the study sample and appear to be involved with mental overload.
Keywords: mental workload; nursing technicians; hospital